Registros notables de mamíferos terrestres del estado de Hidalgo, México. Noteworthy records of terrestrial mammals from state of Hidalgo, Mexico - Aguilar-López, Melany; Rojas-Martínez, Alberto E.; Cornejo-Latorre, Cristian; Sánchez-Hernández, Cornelio; Vite-Silva, Víctor D.; Ramos-Frías, Josefina (Instituto de Ecología, A.C., 2015)
RESUMEN. Documentamos la presencia de nueve especies de mamíferos poco conocidos para el estado de Hidalgo. Los ejemplares fueron capturados o registrados durante los muestreos realizados entre noviembre de 2007 y mayo de 2011, así como entre enero y abril del 2015 en 28 municipios de Hidalgo. Para cada espécimen aportamos información sobre la distribución, medidas somáticas, condición reproductiva y el hábitat. Seis de las nueve especies representan el primer registro para el estado: Leopardus wiedii, Eira barbara, Lontra  longicaudis, Orthogeomys hispidus, Peromyscus beatae y Peromyscus hylocetes. ABSTRACT. We documented the presence of nine mammal species, which are not well known to the state of Hidalgo, Mexico. The specimens  were captured or registered during fieldwork that was conducted between November 2007 to May 2011, as well as January to April 2015 in 28 municipalities of Hidalgo. Information about distribution, somatic measurements, reproductive status and habitat is provided for each specimen. Six of the nine species reported in this study represent the first records for the state: Leopardus wiedii, Eira barbara, Lontra  longicaudis, Orthogeomys hispidus, Peromyscus beatae y Peromyscus hylocetes.